The Causal Effect of Watching TV on Material Aspirations: Evidence from the “Valley of the Innocent” - Walter Hyll; Lutz Schneider (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2012)
The paper addresses the question of whether TV consumption has an impact on material aspirations. We exploit a natural experiment that took place during the period in which Germany was divided. Owing to geographical reasons, TV programs from the Federal Republic of Germany could not be received in all parts of the German Democratic Republic. Therefore, a natural variation occurred in exposure to West German television. We find robust evidence that watching TV is positively correlated with aspirations. Our identification strategy implies a causal relationship running from TV to aspirations. This conclusion resists various sets of alternative specifications and samples. – – Der Beitrag adressiert die Frage, ob Fernsehkonsum einen Einfluss auf materielle Einstellungen ausübt. Die Analyse benutzt ein natürliches Experiment, welches während der deutschen Teilung stattfand. Aus topographischen Gründen konnte das Fernsehprogramm der BRD nicht in allen Teilen der DDR empfangen werden. Deshalb gibt es eine exogene Variation mit Blick auf die Verfügbarkeit von Fernsehprogrammen. Wir finden klare Belege dafür, dass der Konsum westdeutscher Programme positiv mit promaterialistischen Einstellungen korreliert ist. Die Identifikationsstrategie impliziert, dass diese Korrelation als kausaler Einfluss des Fernsehens interpretiert werden kann. Unser Ergebnis erweist sich als robust gegenüber Variationen der Spezifikation und der Daten.
urn:nbn:de:101:1-201212176847
Keywords: C26; D12; I31; 330; natural experiment; TV consumption; material aspirations; Natürliches Experiment; TV-Konsum; materielle Einstellungen